2008
DOI: 10.1111/j.1095-8312.2007.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase in body size of the American marten Martes americana in Alaska

Abstract: Using museum specimens, we studied recent changes in skull size of the American marten Martes americana, in continental Alaska. In Alaska, global warming has resulted in milder winters that may contribute to an improved food supply in the wild. In the present study, we tested the hypothesis that body size of the marten had increased during the second half of the 20th century, in response to global warming. We found that skull size, and by implication body size, increased significantly during the second half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…Recent increases in body size of several species of mammals in temperate climates have been attributed to direct (energy savings) and indirect (through food availability) effects of increased ambient temperature (Yom-Tov 2003;Yom-Tov and Geffen 2006;Yom-Tov et al 2007;Yom-Tov et al 2008), and the results of this study further support this hypothesis. However, as mentioned in the Introduction, this hypothesis is by no means the exclusive explanation for body size in these two species, and the observed trends may be a result of other factors mentioned above.…”
Section: Discussionsupporting
confidence: 71%
“…Recent increases in body size of several species of mammals in temperate climates have been attributed to direct (energy savings) and indirect (through food availability) effects of increased ambient temperature (Yom-Tov 2003;Yom-Tov and Geffen 2006;Yom-Tov et al 2007;Yom-Tov et al 2008), and the results of this study further support this hypothesis. However, as mentioned in the Introduction, this hypothesis is by no means the exclusive explanation for body size in these two species, and the observed trends may be a result of other factors mentioned above.…”
Section: Discussionsupporting
confidence: 71%
“…Not all climate change effects, however, will necessarily be detrimental. For marten in interior Alaska, Yom-Tov et al (2008) found increasing body size in the last half of the 20th century and proposed enhanced prey abundance and reduced energy expenditure due to climate change as the causes. However, we thought a positive effect on marten in our sub-boreal forest was not likely.…”
Section: Population Response Meta-modelmentioning
confidence: 99%
“…Long-term changes in phenology, distribution and/ or morphometrics of animal populations are increasingly reported, and often attributed to global climate change (reviews in Hughes 2000;McCarthy 2001;Walther et al 2002; Thorup et al 2007; see also Prop et al 1998; Thomas and Lennon 1999;Hatzofe and Yom-Tov 2002). Increase in mean body size at the population level has been demonstrated in some species Yom-Tov 2004, 2005;Yom-Tov et al 2008; review in Millien et al 2006), though the opposite has also been reported (e.g. Smith et al 1998;Yom-Tov 2001;Yom-Tov et al 2006a).…”
Section: Introductionmentioning
confidence: 99%